IMPLEMENTASI MODEL PENGABDIAN KEPADA MASYARAKAT BIDANG HUKUM DI PROVINSI KALIMANTAN SELATAN - H M Hadin Muhjad; Rahmida Erliyani; Dermawati Sihite (ABDIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2016)
The principle of rule of law is the recognition of human rights and equality before the law that emphasizes a balanced and equal treatment to every citizen before the law. That is in line with the terms of the provision of legal aid and advocacy to the public asa part of their constitutional right. Therefore it is necessary to grant a good understanding of the entire community to gain their rights to legal assistance and advocacy. Implementation of legal aid is an important part in providing legal benefit for the community. In order to benefit the community law required an appropriate model of legal aid in achieving those goals in this connection referred to the legal service action model. Legal service actions are an attempt to establish a culture of law in both the life of the nation and an attempt awareness of legal rights and obligations of society which is constitutionally recognized.Community service activities in law with legal service actions, conducted by the Facultyof Law as an embodiment of HigherEducationTridarma which in this regard isLambung Mangkurat Univercity through LKBH (Legal aid and consultation bodies) has conducted a series of activities conceived as a legal service actions.